Pulmonary Emboli Manifestation during Spinal Anesthesia for Cesarean Section in two Pregnant Women - Dahi, Mastaneh; Mohajerani, Seyed Amir (Novelty in Biomedicine, 2015)
Background: Pregnancy causes a small increase in risk of venous thromboembolism (VTE), but a large increase in concern upon presentation during cesarean section with symptoms of pulmonary embolism (PE). Pulmonary embolism clinical manifestations during spinal anesthesia could be misleading. We have presented 2 interesting cases of pregnant women underwent spinal anesthesia for cesarean section and manifested with non-specific clinical symptoms of PE during spinal anesthesia mistaken for high spinal scenarios. Cases Report: Two young pregnant women candidate for cesarean section underwent spinal anesthesia. During surgery, patient grows chest discomfort and dyspnea. Anesthesiologist misleaded for high spinal but observed patients during surgery and in recovery. Further investigation detected pulmonary embolism which was further treated in ICU and patients were discharged subsequently. Conclusion: Anesthesiologists cannot safely rule out pulmonary embolism during spinal anesthesia in cesarean section without additional testing, at least not in pregnant women with a relatively high risk of PE.